Plant architectural traits influence residence time of a specialist jumping spider - Omena, Paula M. de; Bernabe, Tiago N. [UNESP]; Kersch-Becker, Monica F.; Recalde, Fatima C.; Antiqueira, Pablo A. P.; Vieira, Camila; Migliorini, Gustavo H. [UNESP]; Benavides-Gordillo, Sandra; Romero, Gustavo Q. (Springer, 2017)
The patch residence time of spiders has long been attributed to prey availability. We provide empirical evidence that plant architecture determines the residence time of a bromeliad-living spider. The residence time of spiders was longer on rosette-shaped plants. Males left their host plant faster than females, likely due to their mate-searching activity. We demonstrate that plant architectural traits mediate the patch-leaving tendency of specialist spiders.
Keywords: Salticidae; Mutualism; Plant selection; Spider-plant interaction; Bromeliad